Innovation for the sake of innovation? How does robotic hepatectomy compare to laparoscopic or open tesection for HCC: a systematic review and meta-analysis - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Hoffmann, Katrin (Cancers, 2022)
Robot-assisted hepatectomy is a novel approach to treat liver tumors. HCC is on the rise as the cause of cancer and mortality and is often preceded by cirrhosis. Robot-assisted hepatectomy has been suggested to offer benefits to cirrhotic patients. We aimed to evaluate current evidence for robot-assisted hepatectomy for HCC and compare it to open and laparoscopic approaches. This systematic review and meta-analysis has been conducted in accordance with most recent PRISMA recommendations and the protocol has been registered at PROSPERO (CRD42022328544). There were no randomized controlled trials available and no study focused on cirrhotic patients exclusively. Robot-assisted hepatectomy was associated with less major complications than the laparoscopic approach, but comparable with open hepatectomy. No difference was seen in overall or minor complications, as well as liver specific or infectious complications. Cumulative survivals were similar in robot-assisted hepatectomy and laparoscopic or open approaches. There is a clear lack of evidence to suggest particular benefits for robot-assisted hepatectomy in cirrhotic patients. Otherwise, the robot-assisted approach has similar complication rates as open or laparoscopic methods. Non-industry driven randomized controlled trials are needed to evaluate the efficacy of robot-assisted liver surgery.
Gesehen am 17.08.2022